2009
DOI: 10.1111/j.1439-0531.2008.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cells of the Bovine Cervical Stroma may have a Secretory, rather than a Contractile Function during Parturition

Abstract: The bovine cervix contains a large amount of smooth muscle cells distributed over an outer muscular layer and within a stromal layer. The stromal layer exhibits no electromyographic (EMG) activity at parturition. This leads to the question whether the stromal smooth muscle cells of the bovine cervix are prepared to contract with parturition, or whether they have another function. To this end, cervical biopsies were repeatedly taken from 10 pregnant cows at day-185 and -275 of gestation, at spontaneous, uncompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(137 reference statements)
1
3
0
Order By: Relevance
“…Moreover, we also found that PGE 2 in intrapartum uterine cervix is also able to be produced or secreted in vascular endothelium, squamous epithelium, glandular epithelium, serosa, mesenchymal cells, and circular and longitudinal smooth muscle. This is in agreement with the observations made by Engelen et al [54] who found that many of the smooth muscle cells distributed over the outer muscular layer and within the stromal layer in the bovine cervix at parturition have a secretory function. In addition, it is possible that the PGE 2 secreted by the caprine uterine cervix has a paracrine and autocrine function in the cervix itself or in ambient tissues and cells.…”
Section: Pge 2 and Its Four Receptorssupporting
confidence: 93%
“…Moreover, we also found that PGE 2 in intrapartum uterine cervix is also able to be produced or secreted in vascular endothelium, squamous epithelium, glandular epithelium, serosa, mesenchymal cells, and circular and longitudinal smooth muscle. This is in agreement with the observations made by Engelen et al [54] who found that many of the smooth muscle cells distributed over the outer muscular layer and within the stromal layer in the bovine cervix at parturition have a secretory function. In addition, it is possible that the PGE 2 secreted by the caprine uterine cervix has a paracrine and autocrine function in the cervix itself or in ambient tissues and cells.…”
Section: Pge 2 and Its Four Receptorssupporting
confidence: 93%
“…One part of each biopsy sample was snap‐frozen in liquid nitrogen, and stored at −80°C until further analysis and the other part was fixed in 4.5% formaldehyde in phosphate‐buffered saline (PBS) for 24 h and embedded in paraffin. These biopsy samples were also used in a previous study (van Engelen et al. 2008a).…”
Section: Methodsmentioning
confidence: 99%
“…The localization of the brown MMP-2 staining was assessed by light microscopy. Since in the cervical stroma, smooth muscle cells (SMC) are oriented in bundles surrounded by connective tissue which contains fibroblasts (Van Engelen et al, 2008), it was possible to estimate which cells stained positive for MMP-2, and if MMP-2 was present in the ECM.…”
Section: Immuno Histochemistry For Mmp-2mentioning
confidence: 99%